Aufbau und Regelung eines sturzvariablen Bahnfahrwerks mit Einzelradlenkung - Borsig, Michael; Trächtler, Ansgar; Geisler, Jens (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Echtzeitsimulation für den modellbasierten Steuergerätetest von Haushaltsgeräten - Koert, Dirk; Löffler, Alexander; Zeineldin, Tarek; Trächtler, Ansgar (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Entwurf einer semiaktiven Federung für ein leichtes Kettenfahrzeug - Illg, Igor; Jäker, Karl-Peter; Trächtler, Ansgar (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Verlässlichkeit im aktiven selbstoptimierenden Spurführungsmodul eines schienengebundenen Fahrzeugs - Sondermann-Wölke, Christoph; Geisler, Jens; Hirsch, Martin; Hemsel, Tobias (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Proceedings of Design for Future - 1. Workshop des GI-Arbeitskreises "Langlebige Softwaresysteme (L2S2)"

A Holistic Software Engineering Method for Service-Oriented Application Landscape Development - Baumann, Andrea; Engels, Gregor; Hofmann, Alexander; Sauer, Stefan; Willkomm, Johannes (Proceedings of the First NAF Academy Working Conference on Practice-Driven Research on Enterprise Transformation (PRET 2009), Amsterdam (The Netherlands))
Enterprises are transforming into enterprises which follow from a business as well as from an IT perspective a service-oriented paradigm. This change towards service-oriented enterprise and IT architectures has to be reflected in the methodologies of developing whole application landscapes as well as individual applications. Quasar (Quality Software Architecture) has been developed as the standard architecture and development method of Capgemini sd&m for individual applications. For the development of service-oriented enterprise application landscapes, Quasar Enterprise has been designed. Both Quasar and Quasar Enterprise are integrated with each other within a holistic software engineering method to seamlessly cover the full development lifecycle of service-oriented application landscapes, from business modeling and service design to actual software development. In this paper, we illustrate how a company-wide ontology of development artifacts serves as the key feature for integrating both methods.

Creating Butterflies in the Core - A Network Coding Extension for MPLS/RSVP-TE - Biermann, Thorsten; Schwabe, Arne; Karl, Holger (NETWORKING 2009, 8th International IFIP-TC 6 Networking Conference, Aachen, Germany, May 11-15, 2009. Proceedings)

“Metriken” – Kennzahlen zur Verbesserung der Softwarequalität, Teile 1 und 2 - Gehrke, Matthias; Güldali, Baris; Meyer, Jan; Sancar, Yavuz; Spijkerman, Michael

"Metriken" - Kennzahlen zur Verbesserung der Softwarequalität, Teile 1 und 2 - Gehrke, Matthias; Güldali, Baris; Meyer, Jan; Sancar, Yavuz; Spijkerman, Michael

Acceptance of Remote Services – Perception, Adoption, and Continued Usage in Organizational Settings - Wünderlich, Nancy
The increasing employment of information and communication technologies in companies and households has led to considerable changes in the way services are conceived, developed, and delivered. Nancy V. Wünderlich employs a multi-method approach comprising an international qualitative study in Germany, USA and China and a longitudinal quantitative study to analyze remote services. She develops the Interactive Technology-Mediated Service Model (ITSUM) to provide a comprehensive approach of explaining both initial acceptance and repeated, continued usage of remote services in organizations. Finally, she derives managerial implications for remote service providers on how to increase remote service acceptance among their customers and facilitate the export of remote services.

Lateral electron tunnelling spectroscopy in etched GaAs/AlGaAs-based nanostructures - Fischer, S F; Deborde, J L; Kunze, U; Reuter, Dirk; Wieck, A D (Journal of Physics: Conference Series)

Lateral electron tunnelling spectroscopy in etched GaAs/AlGaAs-based nanostructures - Fischer, S F; Deborde, J L; Kunze, U; Reuter, Dirk; Wieck, A D (Journal of Physics: Conference Series)

Assmann, A.: Einführung in die Kulturwissenschaft - Tönnies, Merle (Anglistik. International Journal of English Studies)

Lionel Johnson - Flotmann, Christina (Kindlers Literaturlexikon)

Modellbasierte Entwicklung piezoelektrischer Trägheitsmotoren - Hunstig, Matthias; Hemsel, Tobias (6. Paderborner Workshop Entwurf mechatronischer Systeme)
Die Entwicklung piezoelektrischer Trägheitsmotoren basiert derzeit auf Erfahrungswissen und Prototypenbau. Es existiert kein allgemeines Modell und keine Methodik für die systematische Entwicklung dieser Motoren. In diesem Beitrag stellen wir einen Ansatz zur Entwicklung einer solchen Methodik und den von uns aufgebauten Versuchsmotor vor. Der Motor ist modular aufgebaut; er besteht im Wesentlichen aus einer piezoelektrischen Antriebseinheit, einem Antriebsstab und dem zu bewegenden Schlitten. Eine wesentliche Aufgabe bei der modellbasierten Entwicklung von Trägheitsmotoren ist die hinreichende Beschreibung des dynamischen Verhaltens der Antriebseinheit. Um ein geeignetes Modell zu finden, bzw. um nachzuweisen, dass einfache parametrische Modelle genügen, wird die Antriebseinheit des Motors detailliert untersucht. Es zeigt sich, dass der derzeitige Aufbau eine Reihe von Nachteilen aufweist, die durch eine teilweise Neukonstruktion der Antriebseinheit beseitigt oder zumindest entschärft werden können.
Keywords: Piezoelektrischer Tr{\

Structural characterization of cubic and hexagonal GaN thin films grown by IBA–MBE on SiC/Si - Häberlen, M.; Gerlach, J.W.; Murphy, B.; Lindner, Jörg; Stritzker, B. (Journal of Crystal Growth)
Buried ion beam synthesized 3C-SiC layers were revealed to the surface of silicon wafers to provide lattice matched substrates for GaN thin film epitaxy. Both epitaxial SiC/Si(1 1 1) and SiC/Si(0 0 1) growth surfaces with either six- or four-fold crystal symmetry, respectively, were formed. GaN thin film growth was achieved by ion beam assisted molecular beam epitaxy (IBA–MBE) which – owing to the energy and momentum transfer of the ions – allows to deposit epitaxial thin films at particularly low growth temperatures where both the stable hexagonal and the metastable cubic polytype of GaN can be formed. It is shown by X-ray diffraction (XRD) and cross-sectional transmission electron microscopy (XTEM) that using appropriate fluxes of Ga atoms both purely hexagonal and purely cubic GaN films can be grown epitaxially on SiC/Si(1 1 1) and SiC/Si(0 0 1), respectively. Thereby Ga rich growth conditions seem to stabilize the formation of the cubic polytype. It is obvious from XTEM studies that the high density of crystal defects in the SiC layer is not transferred onto the growing GaN films and that the crystalline quality of GaN films improves with increasing film thickness. The influence of surface roughness and wettability, interfacial cavities and the nucleation of twin-type defects at the GaN/SiC interface on the crystalline quality of the GaN thin films is discussed.

Spin-Coupling in Heavily Nitrogen-Doped 4H-SiC - Savchenko, D.V.; Pöppl, Andreas; Kalabukhova, Ekaterina N.; Greulich-Weber, Siegmund; Rauls, Eva; Schmidt, Wolf Gero; Gerstmann, Uwe (Materials Science Forum)
EPR and ESE in nitrogen doped 4H- and 6H-SiC show besides the well known triplet lines of 14N on quasi-cubic (Nc,k) and hexagonal (Nc,h) sites additional lines (Nx) of comparatively low intensity providing half the hf splitting of Nc,k. Frequently re-interpreted as spin-forbidden lines, arising from Nc,k pairs and triads or resulting from hopping conductivity, only recently the theoretical calculation of the corresponding g-tensors lead to a tentative model of distant NC donor pairs on inequivalent lattice sites which are coupled to S = 1 assuming a fine-structure splitting too small to be observed in the EPR and ESE experiments. In this work, we present ESE nutation measurements confirming S = 1 for the Nx center. Analysing the nutation frequencies in comparison with that of the Nc,k (S = 1/2) spectrum as well as the line width of ESE and EPR spectra we obtain a rough estimate between 5×104 cm-1 and 50×104 cm-1 for the fine-structure splitting demonstrating efficient spin-coupling between nitrogen donors in 4H-SiC.

Vacancy clusters created via room temperature irradiation in 6H-SiC - Scholle, A.; Greulich-Weber, S.; Rauls, E.; Schmidt, W.G.; Gerstmann, U. (Physica B: Condensed Matter)
In non-annealed 6H-SiC samples that were electron irradiated at low temperature, a new EPR signal due to a S =1 defect center with exceptionally large zero-field splitting (D= +652104cm1,E=8104cm1) has been observed under illumination. A positive sign of D demonstrates that the spin–orbit contribution to the zero-field splitting exceeds by far that of the spin–spin interaction. A principal axis of the fine-structure tilted by 59 1 against the crystal c -axis as well as the exceptionally high zero-field splitting D can be qualitatively understood by the occurrence of additional close-lying defect levels in defect clusters resulting in comparatively large second-order spin–orbit coupling. A tentative assignment to vacancy clusters is supported by the observed annealing behavior.

GaN-based LEDs grown on 6-inch diameter Si (111) substrates by MOVPE - Zhu, D.; McAleese, C.; McLaughlin, K. K.; Häberlen, M.; Salcianu, C. O.; Thrush, E. J.; Kappers, M. J.; Phillips, W. A.; Lane, P.; Wallis, D. J.; Martin, T.; Astles, M.; et al. (Light-Emitting Diodes: Materials, Devices, and Applications for Solid State Lighting XIII)
The issues and challenges of growing GaN-based structures on large area Si substrates have been studied. These include Si slip resulting from large temperature non-uniformities and cracking due to differential thermal expansion. Using an AlN nucleation layer in conjunction with an AlGaN buffer layer for stress management, and together with the interactive use of real time in-situ optical monitoring it was possible to realise flat, crack-free and uniform GaN and LED structures on 6-inch Si (111) substrates. The EL performance of processed LED devices was also studied on-wafer, giving good EL characteristics including a forward bias voltage of ~3.5 V at 20 mA from a 500 μm x 500 μm device.

Shelagh Delaney 'A Taste of Honey' - Tönnies, Merle (Kindlers Literaturlexikon)